Pengaruh Motor Relearning Programme (MRP) Terhadap Peningkatan Kemampuan Fungsional Pasien Hemiparese Post Stroke di Kilinik Nur Medika Luwuk - Nur Safira Lasimpala; Liza Agustin; Ronald Erwansyah (Pusat Riset dan Inovasi Nasional, 2024)
Post-stroke hemiparesis is a weakness or inability to move on one side of the body, making it difficult to do daily activities, such as eating or dressing. Weakness on one side of the arm and leg can cause loss of balance in walking, impaired ability to pick up objects, decreased precision of movement, muscle weakness, and lack of coordination. Motor Relearning Program (MRP) focuses on relearning certain movements, tasks and motor skills that lead to the ability to perform a task. The motor relearning approach emphasizes training in motor tasks. This technique provides functional training and identification of key motor tasks, such as sitting, standing or walking. Objective: This study was conducted to determine the effect of increasing functional ability using the Motor Relearning Program (MRP) on Post-Stroke Hemiparesis patients at the Nur Medika Luwuk Clinic. Method: The research design used was an experimental method with a One-Group Pre-test and Post Test design model. The sample determination used the total sampling technique with a sample size of 10 respondents aged 45-65 years. The Barthel Index was measured to determine the functional ability of the respondents. The results of the study were analyzed using the Shapiro-Wilk normality test and the Wilcoxon sign rank test. Results: The results of the Wilcoxon sign rank test obtained an Asymp.Sig. (2-tailed) value of 0.003 <0.05, which means that there is an effect of the Motor Relearning Program (MRP) on improving the functional abilities of hemiparesis patients at the Nur Medika Luwuk Clinic.